Problem Penerapan Pembelajaran Pendidikan Agama Islam dengan Pendekatan Saintifik pada Mahasiswa Magang di Madrasah Aliyah Paradigma Palembang - Nazarudin, Nazarudin (Jurnal Pendidikan Agama Islam, 2020)
This study is a case report primarily conducted to analyze the factors which brought about the unsuccessful implementation of learning with an optimal scientific approach administered by the Faculty of Tarbiyah and Teacher Training students during the Internship III at Senior Islamic School Paradigma in Palembang. The research method employed was qualitative research. Data collection was carried out by direct communication techniques through observation and interviews. Meanwhile, the tools employed for data collection were observation guides and interview guides. The final results showed that the majority of Internship III students had inferior knowledge and practice in carrying out scientific learning. Some factors that dominated the lack of optimal learning with a scientific approach were incomprehension, unpreparedness, and the students' inability to manage time effectively. Only 3 (three) out of 15 (fifteen) respondents really understood, were ready and able to carry out procedural and scientific learning at its utmost.